Ekonomika i politika . Ekonomika i politika . Economics and Politics . Экономика и политика - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Constitutional reform in Russia; economic news in Russia and in the world. Contributors: Vasil'ev, Aleksandr (Anchor) Конституционная реформа в России; новости экономики в России и мире. Создатели: Васильев, Александр (Ведущий/Ведущая)